Alain Badiou, Wallace Stevens and the paradoxical productivity of poetic form. Issue 5 (28th July 2016) - Eyers, Tom
ABSTRACT: In this essay, I take the measure of Badiou's approach to literature and art by focusing on his reading of Wallace Stevens. My aim is not to comprehensively explain the place of art in Badiou's wider philosophy; such a project is beyond the ken of a relatively short article. Rather, Badiou's flawed conscription of Stevens to his philosophy of the event will serve as a foil to my own reading of the poet, one that contests what I take to be Badiou's repetition of an earlier critical consensus. Badiou may be said, despite his innovations, to embody an older trend in Wallace Stevens criticism, namely to argue for the poet as what Simon Critchley has called a kind of 'anxious atheist' who sought to forge a temporary bridge between the mind of a disabused modernity, reeling from the death of God, and its recalcitrant objects. I will propose an opposite take, one that takes seriously the incessant interruptions in the form of Stevens' verse, structural dissonances that enable the non-mimetic but nonetheless constructive power of Stevens' poetry to take hold. Such an approach must take seriously both the desire immanent to Stevens' verse to exit language, to find itself in the entanglements of the world, and the parallel and necessary failure of that desire to achieve its aims mimetically.